Pandemic fatigue: a challenge in combatting against covid-19 - Mohd Rohaizat Hassan; Syed Sharizman Syed Abdul Rahim; Mohammad Saffree Jeffree (Universiti Malaysia Sabah, 2021)
The COVID -19 pandemic has hit the world for a period of a year and a half; it has been a triple crisis, with medical, economic, and psychological consequences (Hoof, E.V., 2020). After 18 months of going through a pandemic, this includes not only facing the transmission of SARS CoV-2 virus but also restricted movements. Communities are now facing pandemic fatigue starting as early as the third wave of increased cases in September 2020 (Gerada, C., 2020). Pandemic fatigue is the stage when the initial enthusiasm and eagerness to tackle the crisis is replaced by feelings of exhaustion (Murphy, J.F.A., 2020). In a simple definition, pandemic fatigue is understood as demotivation to follow recommended protective behaviours (Morrison, M., 2011 & Masten, A.S., 2020). It is a natural and expected reaction to sustained and unresolved adversity in people’s lives, evolving gradually over time and affected by several emotions, experiences, and perceptions as well as the cultural, social, structural, and legislative environment (WHO, 2020).